BIOAKTIVITAS ZAT EKSTRAKTIF KULIT Acacia auriculiformis A. Cunn. ex Benth. TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Yanti Hikma; Wasrin Syafii; IGK Tapa Darma (Tengkawang : Jurnal Ilmu Kehutanan, 2012)
This research was undertaken mainly to isolate and identify antitermitic substances that may be prospective as wood natural preservative from the bark of Acacia auriculiformis A. Cunn. ex Benth. The woodmeal of the samples were extracted with acetone. The acetone extract was then fractionated into n-hexane soluble fraction, ethyl ether soluble fraction, ethyl acetate soluble fraction, and insoluble fraction. The antifeedant bioassay test was carried out by treating paper discs with extracts at six level of concentration i.e. 0%, 2%, 4%, 6%, 8%, and 10% (w/w). The bioassay test revealed that ethyl ether soluble fraction exhibited high toxicity to subterranean termite Coptotermes curvignathus Holmgren (concentration of 4% has been indicated very strong activity). Keywords: Bioactivity, extractives, Acacia auriculiformis, termites, Coptotermes curvignathus